Nurses' knowledge of chronic disease management - Saloshni Naidoo; Ozayr H. Mahomed; Shaidah Asmall; Myra Taylor (AOSIS, 2014)
Background: Chronic diseases of lifestyle are detrimentally affecting South Africans. National Health Insurance, which is intended to improve care, requires capacity building for nurses at primary care clinics to ensure appropriate service provision. Objective: This study's objective was to evaluate the impact of the 'Primary Care 101' chronic disease management guideline and training on nurses' knowledge of chronic diseases management. Method: A population-based, unblinded, stratifid cluster randomised controlled trial with intervention (n = 20) and control clinics (n = 10) in three South African districts was conducted over six months in 2012. Nurses in the clinics participated in surveying knowledge on management of tuberculosis, human immunodefiiency virus infection, mental health, epilepsy, diabetes, hypertension and asthma and chronic obstructive pulmonary disease (COPD). All nurses were surveyed at baseline and six months later. Intervention clinic nurses were also surveyed immediately after training and three months post-training. Data were analysed using SPSS version 19 (SPSS Inc., Chicago, IL).Total mean knowledge percentage scores were calculated for each chronic disease. Mean knowledge percentage score changes between baseline and six months amongst all nurses and between intervention and control clinic nurses were compared using the paired samples t-test and independent samples t-test respectively. Results: There were signifiant improvements in nurses' knowledge of hypertension and diabetes management over six months. Knowledge about asthma and COPD management decreased in all districts and nurse categories. Conclusion: The improvements in nurses' knowledge can ensure improved patient management, but attention to asthma and COPD management is required. Agtergrond: Chroniese lewenstylsiektes beïnvloed Suid-Afrikaners nadelig. Die nasionale gesondheidsversekering, wat ten doel het om sorg te verbeter, vereis kapasiteitsbou vir verpleegsters by primêre-sorg-klinieke om sodoende toepaslike dienslewering te verseker. Doelwitte: Hierdie studie se doel was te evalueer wat die impak van die 'Primary Care 101' chroniese siekte bestuursriglyn, asook opleiding is op verpleegsters se kennis van hoe om chroniese siektes te bestuur. Metode: 'n Bevolkingsgebaseerde, onverblinde, ewekansige gekontroleerde trossteekproef met ingrypings- (n = 20) en kontrole-klinieke (n = 10) is oor 'n tydperk van ses maande in 2012 in drie Suid-Afrikaanse distrikte uitgevoer. Verpleegsters in hierdie klinieke het deelgeneem aan 'n opname oor hul kennis oor die bestuur van tuberkulose, menslike immuniteitsgebreksvirus-infeksie, geestesgesondheid, epilepsie, diabetes, hoë bloeddruk, asook asma en chroniese obstruktiewe longsiekte (COPD). Alle verpleegsters is by die basislyn ondervra en ses maande later. Intervensie kliniekverpleegsters is ook ondervra onmiddellik na die opleiding en drie maande post-opleiding. Data is ontleed met behulp van SPSS, weergawe 19 (SPSS Inc, Chicago, IL). Totale gemiddelde kennis persentasietellings is vir elke chroniese siekte bereken. Veranderinge in die gemiddelde kennis persentasietellings tussen die basislyn en ses maande later is onder alle verpleegsters, asook tussen ingrypingsen kontrole-kliniekverpleegsters vergelyk met behulp van die gepaarde steekproef t-toets en die onafhanklike steekproef t-toets onderskeidelik. Resultate: Daar was 'n aansienlike verbetering in verpleegsters se kennis oor die bestuur van hoë bloeddruk en diabetes na ses maande. Kennis oor die bestuur van asma en COPD het in alle distrikte en verpleegster-kategorieë afgeneem. Gevoltrekking: Die verbetering in die verpleegsters se kennis kan verbeterde pasiëntbestuur verseker, maar die bestuur van asma en COPD vereis verdere aandag.